Implementation of Student Management based on Islamic Religious Education Values in Fostering Students Achievement and Character at SMA Negeri 1 Simo - Naditya Windy Hapsari; Muhammad Wildan Shohib (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to explore the implementation of student management based on Islamic Religious Education (PAI) values at SMA Negeri 1 Simo, as well as to examine its contribution to student achievement and character development. Using a qualitative descriptive approach, the research focused on key informants, including the Vice principal for student affairs and IRE teachers, to understand the planning, implementation, and evaluation of student programs related to discipline, morals, student achievement, and talent. Using the Miles, Huberman, and Saldana data analysis model, namely interviews, limited observation, and documentation analysis, all methods were used to collect data. The findings show the systematic implementation of student management with the integration of PAI values, which can be seen in the transparent PPDB process, structured organization, and collaborative efforts between teachers. The implementation of this management contributes significantly in various aspects, including improving student discipline, academic and non-academic achievement, and strengthening character building based on the values of responsibility, respect, and moral awareness. In conclusion, student management based on PAI values has succeeded in creating an integrative, humanistic, and holistic educational environment that not only supports academic achievement but also ensures the development of noble character.